Bio-protective solutions for carrot spoilage: exploring the antifungal properties of ginger, garlic, onion, and Moringa - Eugenia Njoku; Florence Mbaoji; Justus Nweze; Bonaventure Echezona; Kayode Baiyeri (Journal of Horticulture and Postharvest Research)
Purpose: To address postharvest losses in the carrot supply chain caused by pathogenic fungi, this study evaluates the antifungal potential of ethanol extracts from Allium cepa, Zingiber officinale, Allium sativum, and Moringa oleifera against carrot spoilage fungi, including Aspergillus niger, Aspergillus fumigatus, Aspergillus flavus, Fusarium oxysporum, and Fusarium solani. Research Method: Filtered plant extracts were obtained using ethanol extraction method. This study evaluated the efficacy of various plant extracts in reducing microbial load and inhibiting fungal growth on carrot roots using standard microbiological procedures, including agar well diffusion and broth microdilution techniques. Findings: The study demonstrated that ethanol extracts, particularly from ginger, significantly (p < 0.05) reduced fungal load on carrot roots. The inhibition zone analysis revealed that ginger and Moringa extracts, along with ketoconazole, effectively inhibited A. niger and A. fumigatus, with ketoconazole producing the largest inhibition zones. Ginger showed the highest antifungal effectiveness, with minimal inhibitory concentrations ranging from 31.25 mg/ml to 250 mg/ml, particularly against A. niger and A. fumigatus, demonstrating higher antifungal activity compared to other treatments. Garlic consistently exhibited an MIC of 250 mg/ml against all test fungi. Additionally, the minimum fungicidal concentration results highlighted ginger extract’s potent biocidal effects, especially against A. flavus, with an MIC of 62.5 mg/ml. Research limitations: The study is limited to in vitro assessments; field conditions may affect the efficacy of the extracts due to environmental factors. Originality/Value: This research highlights ginger’s potential as a natural antifungal agent, offering practical applications for improving carrot preservation and reducing postharvest losses.